A spectroscopic study of square planar rhodium(I) complexes - Hall, Philip Simon (Department of Chemistry, 2017)
Ninety square planar Rh(I) complexes of the type cis-[Rh(CO)₂(X)(L)], [Rh(COD)(X)(L)], [Rh(CO)₂(L)₂]ClO₄ and [Rh(COD)(L)₂]ClO₄ (X is Cl or Br; COD is 1,5-cyclooctadiene; L is aniline, pyridine, pyridine N-oxide, imidazole and ammonia), as well as their isotopically labelled derivatives (¹³CO, ²H and ¹⁵N) were prepared, characterized by microanalysis and melting point, and investigated by the following spectroscopic techniques: infrared, Raman, ultraviolet, mass spectrometry, and 1H, ¹³C and ¹⁵N nmr spectroscopy. The comprehensive isotopic labelling studies allowed unambiguous assignment of the infrared modes in the 4000-50 cm⁻¹ region. The infrared assignments are discussed with reference to their vᴰ/Vᴴ ratios, the various ligands and halogens used, the charges on the complexes, and are compared to similar compounds. The 1H, ¹³C and ¹⁵N nmr runs were performed at room and low temperatures. Fluxionality of the ligands (L) was observed and the exchange process was monitored by variable temperature nmr. The enthalpy and entropy values for the intermolecular exchange of L in the complexes cis-[Rh(CO)₂(X)(L)] were obtained by a complete computer simulated band shape analysis of the carbonyl region of the ¹³C nmr spectra. The non-equivalence, and specific assignment of the carbonyl groups in the cis- [ Rh(CO)₂(X)(L)] complexes were determined by recording the variable temperature ¹³C nmr spectra of the doubly enriched species cis[Rh(¹³CO)₂(X)(¹⁵N-ligand)]. ²J(¹³C-Rh-¹⁵N) values are reported for the first time. The ¹J(¹⁵N-¹⁰³Rh) coupling constants are rationalized in terms of the metal-nitrogen bonding, and correlate with the s-character of the bonding electron on nitrogen. While the solution electronic spectra reveal that the complexes are discrete monomeric entities in solution, there are indications of metal-metal interactions in the solid-state. The normal coordinate analysis study of the complexes cis-[Rh(CO)₂(X)(L)] involved the calculation of a general valence force field by applying the eigenvector method of Becher and Mattes. The results show that point-mass-modelling and simplified force field, as assumed in our treatment, describes, to a good approximation, the vibrational properties of the complexes. The potential energy distribution provided further support for the proposed infrared assignments of the complexes.